2023
DOI: 10.1021/acschemneuro.2c00691
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PINK1-Mediated Mitophagy Contributes to Postoperative Cognitive Dysfunction through Activation of Caspase-3/GSDME-Dependent Pyroptosis

Abstract: PTEN-induced kinase 1 (PINK1)-mediated mitophagy and caspase-1/gasdermin D canonical pyroptosis pathways have been implicated in the pathogenesis of postoperative cognitive dysfunction (POCD). However, gasdermin E (GSDME), another recently identified executioner of pyroptosis that can be specifically cleaved by caspase-3, is highly expressed in the brain and neurons. This study aimed to ascertain whether PINK1-dependent mitophagy governs postoperative cognitive capacity through caspase-3/GSDME. Twelve month ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Given the crosstalk between apoptosis and pyroptosis established by caspase-3/8, apoptosis may serve as an intermediate link between mitophagy and pyroptosis. Indeed, there have been studies revealing novel mitophagy-pyroptosis regulatory pathways, such as the caspase-3/GSDME axis and caspase-9/GSDME axis, both of which are dependent on apoptosis [ 52 , 53 ]. These discoveries suggest that other pyroptosis pathways may also be regulated by mitophagy through different mechanisms, which have been overlooked thus far.…”
Section: The Regulatory Roles Of Mitophagy In Rcdmentioning
confidence: 99%
“…Given the crosstalk between apoptosis and pyroptosis established by caspase-3/8, apoptosis may serve as an intermediate link between mitophagy and pyroptosis. Indeed, there have been studies revealing novel mitophagy-pyroptosis regulatory pathways, such as the caspase-3/GSDME axis and caspase-9/GSDME axis, both of which are dependent on apoptosis [ 52 , 53 ]. These discoveries suggest that other pyroptosis pathways may also be regulated by mitophagy through different mechanisms, which have been overlooked thus far.…”
Section: The Regulatory Roles Of Mitophagy In Rcdmentioning
confidence: 99%
“…In addition, a review by Chen and Xu ( 39 ) reported on the ability of inflammation to stimulate the expression of caspase-1 precursors, promote the activity of caspase-1 and increase pyroptosis, and highlighted the pathological effect of caspase-1-mediated pyroptosis in vascular disease. Furthermore, androgen deprivation may cause inflammation and endothelial dysfunction via the acceleration of caspase-1 activation and induction of the pyroptosis of endothelial cells ( 31 ). Collectively, these findings may provide a novel theoretical basis for elucidating the mechanisms underlying inflammation-induced ED.…”
Section: Canonical Pyroptosis Pathwaymentioning
confidence: 99%
“…Inflammasome activation in the canonical signaling pathway may induce the release of functional caspase-1 in vivo , the activation of immune cells, and the secretion of chemokines, inflammatory factors and adhesion molecules. This exacerbates the inflammatory response, leading to severe inflammation ( 31 ). A previous study demonstrated that activation of the pyroptosis signaling pathway is associated with the development of ED ( 32 ).…”
Section: Introductionmentioning
confidence: 99%